Analisis Laporan Keuangan Sebelum, Selama dan Sesudah Pandemi Covid-19 Dalam Menilai Kinerja Keuangan Industri Food and Beverage Yang Terdaftar di Bursa Efek Indonesia (BEI) : Studi Kasus PT Sarimelati Kencana Tbk, Periode 2018-2023 - Himawan Pradipta; Merrissa Puji Ambarwati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Purpose_ This study was conducted with the aim of determining whether there is a difference in the financial performance of PT Sarimelati Kencana Tbk (PZZA) before, during, and after the Covid-19 pandemic. Furthermore, this study also aims to analyze whether the Covid-19 pandemic has an impact on the company's financial performance. Method_ The researcher used a quantitative descriptive analysis method to evaluate the financial performance of PT Sarimelati Kencana Tbk (PZZA). Conducting a financial performance assessment is considered important for a company to get a comprehensive picture of its financial position. This assessment is carried out using various methods, one of which is financial statement analysis. Financial statement analysis involves measuring liquidity, solvency, and profitability ratios. These ratios provide information about the company's ability to meet its obligations, manage its assets, and generate profits. Findings_ The financial performance of PT Sarimelati Kencana Tbk (PZZA) experienced a significant decline during the 2018-2023 period, mainly influenced by the impact of the Covid-19 pandemic. It can be said that the decline in the liquidity ratio indicates that there is difficulty for the company in meeting its short-term obligations. The increase in the solvency ratio indicates the company's increasing dependence on debt and the risk of default. It can be said that a decrease in the activity ratio indicates the company's inability to optimally utilize its assets to generate profits. A decrease in the profitability ratio indicates that the company has difficulty generating adequate profits. The company needs to increase capital, maximize sales turnover, and control costs.Implications_ This study provides theoretical contributions by enriching knowledge about financial statement analysis in the context of the Covid-19 pandemic. The findings of this study can be used as a consideration in formulating policies and strategies to improve the company's financial performance during the pandemic. Practically, this study is expected to help PT Sarimelati Kencana Tbk to increase its profitability in the post-pandemic period.Originality_ This study originally uses financial ratios to assess the company's financial performance.Research Type_ Empirical Study.